Pengolahan Limbah Plastik Berbasis Ekonomi Sirkular: Kolaborasi Pengabdian Bersama Rappo ID - Syahnur, Khaerunnisa Nur Fatimah; Syarif, Rahmat; Malik, Anhar Januar; Fitriyani, Fitriyani; Riana, Mirandha Ariesca; Arifin, Iskandar; Sari, Mulyana (Lembaga Dongan Dosen, 2025)
This community service activity aims to increase community awareness and skills in managing household waste, especially plastic waste, through a circular economy approach. Departing from the issue of sustainability and low recycling practices at the household level, the Retail Management Study Program of Kalla Institute of Technology and Business collaborated with Rappo ID to organize a workshop themed “Rethinking the Plastic Bag”. A total of 25 participants were actively involved in the practical training of processing plastic waste into valuable products such as recycled bags and wallets. Participatory and experiential learning methods were used to encourage contextual learning and social transformation. The evaluation results showed an increase in participants' knowledge, skills, and attitude change towards the importance of the 3R principles (Reduce, Reuse, Recycle). This activity not only produces recycled products, but also forms an adaptive and environmentally conscious community of learners. The presence of Rappo ID as an industrial partner also strengthens the validity of the activity and opens opportunities for social entrepreneurship based on environmentally friendly products. This program is a concrete form of implementation of Education for Sustainable Development (ESD) and supports the achievement of the Sustainable Development Goals (SDGs), especially in terms of responsible consumption and production.